Antibacterial Activity of Red Algae Extract (Eucheuma cottonii) Against Propionibacterium acnes and Staphylococcus epidermidis Bacteria - Andreas Lapu Dwitama Bongga; Ivonne Mona Selly Panjaitan; Joshua H. L. Tobing (Jurnal Biologi Tropis, 2026)
Acne is a frequent skin issue characterized by inflammation, linked to an overproduction of oil and the growth of bacteria, especially Propionibacterium acnes and Staphylococcus epidermidis. This study aimed to evaluate the antibacterial activity of red algae (Eucheuma cottonii) extract at concentrations of 25%, 35%, and 45% against these acne-causing bacteria. The extraction process utilized the maceration technique with 96% ethanol over a period of 72 hours. The evaluation of antibacterial activity was performed through the Kirby–Bauer disk diffusion technique. The results demonstrated that all tested concentrations produced inhibition zones classified as moderate against both bacteria. The highest antibacterial activity was observed at the 45% concentration, with mean inhibition zones of 7.3 ± 0.87 mm for P. acnes and 8.2 ± 1.67 mm for S. epidermidis. Statistical analysis using one-way ANOVA indicated no significant differences in antibacterial activity among the tested concentrations for both P. acnes shown p value is .171 (p > 0.05) and S. epidermidis shown p value is .053 (p > 0.05). These findings suggest that E. cottonii extract possesses moderate antibacterial activity and has potential as a natural active ingredient for the development of anti-acne topical formulations, although increasing concentration within the tested range does not significantly enhance its effectiveness.